PERAN DIVISI DESAIN DALAM PENGEMBANGAN KONTEN VISUAL INSTAGRAM @KOMINFOBOGOR DAN @TAKISKOTABOGOR SEBAGAI SARANA INFORMASI PUBLIK - Wina Athifah Zahrah; Suparman (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
Abstract Social media now serves as one of the main channels for distributing public information, including by local government agencies. The Bogor City Communication and Information Agency (Diskominfo) uses Instagram @kominfobogor and @takiskotabogor to convey information to the public through visual content. However, the success of message delivery does not only depend on the existence of the platform, but also on the quality of visual design, which includes the stages of the process and the application of design principles. This study aims to describe the role of the Design Division in developing visual content on the Instagram accounts @kominfobogor and @takiskotabogor as public information media, as well as to identify the challenges and solutions encountered in developing visual content on Instagram @kominfobogor and @takiskotabogor as public information tools. The method used is qualitative descriptive by conducting in-depth interviews with the design division and conducting direct observations of the content production workflow. The analysis in this study refers to the theory of Millerson & Owens (2009), which highlights three stages of production (pre-production, production, and post-production), as well as Sitepu (2004), which describes five main principles: simplicity, balance, emphasis, rhythm, and unity. The research findings show that the Design Division plays an important role in ensuring the effectiveness of public communication through visual content that is well-planned, consistent, and in line with the institution's identity. The obstacles identified include limitations in work tools, differences in views between teams, and a lack of visual referencessample, dependent and independent variables, how to measure the variables, and techniques on data analysis. Result: it contains the main result of the research.